Integration of Internet and telecommunications an architecture for hybrid services. - Gbaguidi, C. (IEEE Journal on selected areas in communications)
We propose an architecture for hybrid services, i.e., services that span many network technologies, such as the public switched telephone network (PSTN), cellular networks, and networks based on IP. These services will play an important role in the future because they leverage on the existing infrastructures rather than requiring new and sophisticated mechanisms to be deployed. We explore a few issues related to hybrid services and propose a platform as well as a set of components to facilitate their creation and deployment. The existing infrastructure is only required to generate specific events when requests for hybrid services are detected. We present the design of a service layer, based on Java, that handles the treatment of these special requests. Our service layer is provided with a set of generic components realized according to the JavaBeans model. We illustrate the strength of our architecture by discussing two hybrid-service examples: a calendar service and a call forwarding service